Interaction Design and Requirements Elicitation Integrated through SPIDe: a feasibility study - Rosa, Jean C. S.; do Rêgo, Beatriz B.; Garrido, Filipe A.; Valente, Pedro D.; Nunes, Nuno J.; Matos, Ecivaldo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
SPIDe is a semio-participatory methodological process initially composed for the interaction (re)design of educational software. However, some SPIDe studies indicated that it is also possible to elicit requirements through its application due to its participatory characteristics. In this paper, we present an investigation about the feasibility of using SPIDe for requirements elicitation, presenting an exploratory case study of requirements elicitation integrated into interaction design. The data was collected in logbooks, semistructured interviews, a technology acceptance model questionnaire, and analyzed using thematic analysis. The results show that the use of SPIDe for requirements elicitation integrated into interaction design is feasible. Besides that, they indicate some improvements to the overall process.